Oral versus rectal laxatives for functional constipation in child - Wiji Joko Pranoto; Supriatmo Supriatmo; Melda Deliana; Atan Baas Sinuhaji (Paediatrica Indonesiana, 2016)
Background Functional constipation is a common childhood condition. Benefits of oral and rectal laxatives in terms of recovery and recurrence in children with functional constipation are still controversial.Objective To compare the effectiveness of oral and rectal laxatives in terms of recovery and recurrence in children with functional constipation.Methods Children aged 8 to 17 years who met the Rome III criteria for functional constipation were enrolled in this open randomised trial. Data was collected through questionnaires, interviews, and physical examinations. The participants were randomly assigned to receive stimulant laxatives (5 mg bisacodyl) either orally for three consecutive days or rectally in a single dose. Subjects kept daily defecation records for 7 days, and were followed up on days 14, 21, 28, 35, and 42. Comparisons of defecation patterns and recurrence of constipation between groups were assessed using Chi-square test.Results Of 99 subjects, 46 children (5 boys, 41 girls) received oral laxatives (group I) and 45 children (8 boys, 37 girls) received rectal laxatives (group II). Four children in each group dropped out. Baseline characteristics are comparable between the groups. Rate of recovery in the first 7 days was higher in the oral compared to rectal groups [84.8% versus 73.3%, respectively, but this was not statistically sininficant (P=0.278)]. In the second week, the recurrence of constipation was significantly higher in the rectal (57.5%) than in the oral laxative group (42.5%) (P=0.026).Conclusion Although recovery tends to occur more with oral compared to rectal laxative agents, the difference was not statistically significant. Higher recurrence in the second week after treatment occurred with rectal laxative agent. [Paediatr Indones. 2016;56:162-6.].